Assessing the antibacterial efficacy of nano propolis concentrations on Streptococcus mutans - Putra, Mohammad Gerald Athallah; Aulia, Zahra Maulida; Widjiastuti, Ira; Pribadi, Nirawati; Cahyani, Febriastuti (Conservative Dentistry Journal, 2024)
Background: Dental caries is a common disease among the Indonesian population, with a prevalence of dental caries in Indonesia reaching 88.8%. Streptococcus mutans is one of the types of bacteria found in caries lesions. Nano propolis has antibacterial properties that can help inhibit the growth of Streptococcus mutans bacteria, reducing the risk of dental caries. Objective: This study aims to determine the effective concentration of nano propolis ranging from 2.5% to 0.625%. Methods: The research evaluates various concentrations of nano propolis, and the minimum concentration that inhibits the growth of Streptococcus mutans is observed using the colony count method. Results: The growth of Streptococcus mutans at a concentration of 2.5% nano propolis was 0, at 1.8% it was 6, at 1.25% it was 11.4, and at 0.625% it was 42. The positive control group containing BHIB media and Streptococcus mutans bacteria showed an average colony growth of 161. Conclusion: Nano propolis at a concentration of 1.25% is effective in inhibiting the growth of Streptococcus mutans.